2018
DOI: 10.1038/s41598-018-26624-w
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the RSRSP stretch is critical for splicing regulation by RNA-Binding Motif Protein 20 (RBM20) through nuclear localization

Abstract: RBM20 is a major regulator of heart-specific alternative pre-mRNA splicing of TTN encoding a giant sarcomeric protein titin. Mutation in RBM20 is linked to autosomal-dominant familial dilated cardiomyopathy (DCM), yet most of the RBM20 missense mutations in familial and sporadic cases were mapped to an RSRSP stretch in an arginine/serine-rich region of which function remains unknown. In the present study, we identified an R634W missense mutation within the stretch and a G1031X nonsense mutation in cohorts of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(114 citation statements)
references
References 69 publications
(101 reference statements)
10
102
1
Order By: Relevance
“…The C-terminal zinc finger is essential for RBM20 function , however so far neither of the two zinc fingers have been shown to bind RNA. The RS domain is required for nuclear localization (Murayama et al, 2018) and likely mediates protein-protein interactions (Maatz et al, 2014). We have shown that inclusion of the unphosphorylated RS domain does not directly affect affinity to AUCUUA RNA ( Table 1).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The C-terminal zinc finger is essential for RBM20 function , however so far neither of the two zinc fingers have been shown to bind RNA. The RS domain is required for nuclear localization (Murayama et al, 2018) and likely mediates protein-protein interactions (Maatz et al, 2014). We have shown that inclusion of the unphosphorylated RS domain does not directly affect affinity to AUCUUA RNA ( Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Most of the RBM20 mutations implicated in cardiomyopathy are localized within the RS region, and these mutants mainly disrupt nuclear localization (Murayama et al, 2018). To see if the addition of the RS region could in general affect RNA binding, we prepared a construct with the C-terminus extended to residue 649.…”
Section: Residues Implicated In Disease Have Little Effect On Rna Binmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24] Loss of RBM20 function leads to mis-splicing of target genes in humans and rodent models. [22][23][24][25] RBM20 is composed of two zink finger domains, one RNA-recognition motif (RRM)-type RNA binding domain and an arginine-/serine-(RS)-rich region. In 2019, two mutational hot spot regions in exons 9 and 11 of RBM20 have been recognized.…”
mentioning
confidence: 99%